Migration and human capital in an endogenous fertility model - Luca Marchiori; Patrice Pieretti; Benteng Zou (Bielefeld University, Institute of Mathematical Economics (IMW), 2008)
How do high and low skilled migration affect fertility and human capital in migrants' origin countries? This question is analyzed within an overlapping generations model where parents choose the number of high and low skilled children they would like to have. Individuals migrate with a certain probability and remit to their parents. It is shown that a brain drain induces parents to have more high and less low educated children. Under certain conditions fertility may either rise or decline due to a brain drain. Low skilled emigration leads to reversed results, while the overall impact on human capital of either type of migration remains ambiguous. Subsequently, the model is calibrated on a developing economy. It is found that increased high skilled emigration reduces fertility and fosters human capital accumulation, while low skilled emigration induces higher population growth and a lower level of education.
urn:nbn:de:hbz:361-14185
Keywords: F22; J13; J24; 330; Migration; Human capital; Fertility; Auswanderung; Humankapital; Rücküberweisung (Migranten); Bildungsinvestition; Fruchtbarkeit; Brain Drain; Theorie; Entwicklungsländer